CONTROVERSY ON COMMUNITY ASSESSMENTS TO TRADITIONAL MEDICINE OF IDA DAYAK FROM THE ANALYSIS OF TAFSIR AL-AHKAM - Sangaji, Ruslan (Institut Agama Islam Negeri Bone, 2023)
This paper aims to examine how the analysis of tafsÄ«r al-ahkÄm of the controversy over the community's assessment of traditional healing techniques in the style of Ida Dayak medicine. This research is included in the type of qualitative research that is deductive in nature. The data collected comes from library data which comes from books, articles and online data. The data is presented in the form of a description. The chosen research target was the style or technique of treatment which gave birth to controversy in the community which was conducted by Ida Dayak. Data and information about Ida Dayak were obtained through online sources. Ida Dayak's treatment system as viral through social media has drawn controversy because it has unique methods and techniques. Its uniqueness is reflected in the visualization of Mrs. Ida's movements which reflect the typical dance coupled with traditional Dayak women's costumes. Ida Dayak uses Allah's name in the healing process by saying basmalah, and according to Islamic theology, believes that He is the Great Healer. In the perspective of Islamic law, treatment that does not carry elements of shirk, according to Islamic law, the treatment is valid. The healing that was produced through traditional medical techniques was born from a form of endeavor for both Ida's mother and the patient. The Indonesian government has supported the traditional medicine system through a number of regulations in creating healthy human beings.